2016
DOI: 10.1111/ele.12575
|View full text |Cite
|
Sign up to set email alerts
|

Ecological interactions and the fitness effect of water‐use efficiency: Competition and drought alter the impact of natural MPK12 alleles in Arabidopsis

Abstract: The presence of substantial genetic variation for water-use efficiency (WUE) suggests that natural selection plays a role in maintaining alleles that affect WUE. Soil water deficit can reduce plant survival, and is likely to impose selection to increase WUE, whereas competition for resources may select for decreased WUE to ensure water acquisition. We tested the fitness consequences of natural allelic variation in a single gene (MPK12) that influences WUE in Arabidopsis, using transgenic lines contrasting in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 55 publications
(126 reference statements)
1
57
0
Order By: Relevance
“…Competition between plants can affect WUE and overall plant performance. When multiple alleles of MPK12 were grown in various combinations of drought and competition, it was found that alleles with high WUE did better in the absence of competition and lines with low WUE did better in competition [154]. All of the above examples indicate a distinct need to evaluate all of the genes discussed in this review in a context of ecophysiology with particular attention to the potential costs in regards to growth and yield.…”
Section: Discussionmentioning
confidence: 85%
“…Competition between plants can affect WUE and overall plant performance. When multiple alleles of MPK12 were grown in various combinations of drought and competition, it was found that alleles with high WUE did better in the absence of competition and lines with low WUE did better in competition [154]. All of the above examples indicate a distinct need to evaluate all of the genes discussed in this review in a context of ecophysiology with particular attention to the potential costs in regards to growth and yield.…”
Section: Discussionmentioning
confidence: 85%
“…Competitive response could simply reflect general stress tolerance. However, some evidence suggests a trade-off between tolerance of competition and tolerance of abiotic stress (Liancourt et al 2005;Campitelli et al 2016). Species with deep root systems may tolerate competition with neighbours by having access to nutrients in deeper soil layers, while low SRL and branching may be associated with high levels of mycorrhizal colonisation, which could compensate for nutrient shortages under competition (Maherali 2014;Koziol and Bever 2015;Cortois et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The situation may be different in early-successional or annual communities, where size effects may dominate (Goldberg 1996). However, trade-offs with other functions, such as tolerance of herbivore damage (Rose et al 2009), timing of reproduction (Chaney and Baucom 2014;Tracey and Aarssen 2014) and resource use efficiency (Ryser 1996;Campitelli et al 2016) may still limit the selective advantage of large size. We therefore need to move beyond the paradigm of fast growth being equivalent to competitive superiority to recognize the importance of traits conferring competitive tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…We found no evidence for QTL influencing A and g s under drought, but plants with lower water use efficiency under drought were similar to drought insensitive genotypes under well-watered conditions and may have shown differences in gas exchange that were below the detection threshold for QTL in an F 1 design. While breeding for improved water use efficiency in crops requires consideration of variation in plant structure and phenology [58] as well as iWUE, the detection of a QTL for iWUE segregating in Alamo germplasm represents a potential step toward genetic approaches to determine the importance of resource use efficiency in switchgrass [59].…”
Section: Relevance Of G×e In Leaf Phenotypesmentioning
confidence: 99%